Bioinformatics-Driven Identification of p62 as A Crucial Oncogene in Liver Cancer - Wang, Ling; Hensley, Culton R.; Howell, Mary E.; Ning, Shunbin (Frontiers in Oncology, 2022)
Liver hepatocellular carcinoma (LIHC) is the major form of liver cancer that is the fourth most common cause of cancer death worldwide. It has been reported that the multifunctional protein p62 (also known as SQSTM1) plays a cancer-promoting role in LIHC, but the detailed mechanisms underlying p62 interaction with LIHC remains unclear. To gain a comprehensive understanding of p62 interaction with LIHC in clinical settings, we performed bioinformatic analyses using various online algorithms derived from high throughput profiling. Our results indicate that p62 expression is significantly upregulated, partially due to its promoter demethylation, rather than p62 gene mutation, in LIHC. Mutation of TP53, CTNNB1, or ALB significantly correlates with, and mutation of AXIN1 reversely correlates with, the p62 expression level. Its upregulation occurs as early as liver cirrhosis, and go through all stages of the carcinogenesis. HCV infection makes a significant contribution to p62 upregulation in LIHC. We further identified p62-associated molecular signatures in LIHC, including many genes that are involved in antioxidant stress and metabolism, such as SRX1 and TXNRD1. Regarding to the clinical outcome, p62 expression level reversely correlates with the survival of LIHC patients (p<0.01). Importantly, we experimentally validated that p62 depletion in liver cancer cell lines downregulates the expression of SRX1 and TXNRD1 at both transcriptional and translational levels, and reduces cell proliferation. As the potential mechanisms underlying the tumor-promoting role of p62, we show that p62 upregulation is remarkably associated with reprogramming of pathways mediated by p53, Wnt/β-catenin, and Keap1-NRF2, which are crucial for oncogenesis in many contexts. Our findings provide a comprehensive insight into the interaction between p62 and LIHC, offering valuable information for understanding of LIHC pathogenesis.